Assessing the Efficacy of RoboTeach Extension Project on Public School Teachers - Michelle C. Gonzales; Edilberto Z. Andal; Delon A. Ching; Magdalena P. Gaffud; Eudora C. Tabo (International Journal of Educational Management and Development Studies, 2021)
The integration of robotics in the education was one of the aspirations of the K-12 institution in the Philippines. The RoboTeach Extension Project was established to address the challenges associated with the implementation of robotics in K-12 education. This study explores the teachers’ perception of the efficacy in the implementation of the project which focused on training the Department of Education (DepEd) teachers in San Pablo City Laguna, Philippines on the basic concepts and applications of robotics and automation. The topics and learning activities covered during the ten-day training were based on the self-assessment survey results on the level of knowledge of teachers. The study used a descriptive method of research using a quantitative approach and adopted the LSPU Extension Services Evaluation Survey Questionnaire to determine the respondents’ perception of the level of project efficacy. The data were obtained from twenty-five DepEd teachers and analyzed using descriptive statistics such as frequency count, per cent, weighted mean and ANOVA. The respondents were highly satisfied with meeting expectations to attain objectives, training and workshop contents, learning activities, methodologies, instructional materials used, resource person and trainers, training management team, and training management team and training facilities and services. Further, there was no significant difference among their level of satisfaction from day 1 to 5 of the training sessions. Respondents viewed the training as very successful, as evident from the consultation and culminating activity. Thus, the sustainability on the implementation of the project was highly recommended.